2021
DOI: 10.1038/s41467-021-22888-5
|View full text |Cite
|
Sign up to set email alerts
|

Elp2 mutations perturb the epitranscriptome and lead to a complex neurodevelopmental phenotype

Abstract: Intellectual disability (ID) and autism spectrum disorder (ASD) are the most common neurodevelopmental disorders and are characterized by substantial impairment in intellectual and adaptive functioning, with their genetic and molecular basis remaining largely unknown. Here, we identify biallelic variants in the gene encoding one of the Elongator complex subunits, ELP2, in patients with ID and ASD. Modelling the variants in mice recapitulates the patient features, with brain imaging and tractography analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 98 publications
6
41
0
Order By: Relevance
“…The analyses confirmed that no microcephaly was evident, with no significant changes found in the cerebral cortex or hippocampus of the mutant mice (Appendix Fig ). Similar to our previous findings in the Elp2 and Elp6 mutants (Kojic et al , 2018, 2021), widespread Purkinje neuron (PN) degeneration was observed in the cerebella of Elp6L118W animals (Appendix Fig ).…”
Section: Resultssupporting
confidence: 90%
“…The analyses confirmed that no microcephaly was evident, with no significant changes found in the cerebral cortex or hippocampus of the mutant mice (Appendix Fig ). Similar to our previous findings in the Elp2 and Elp6 mutants (Kojic et al , 2018, 2021), widespread Purkinje neuron (PN) degeneration was observed in the cerebella of Elp6L118W animals (Appendix Fig ).…”
Section: Resultssupporting
confidence: 90%
“…ASD remains a ‘disease of theories’, as multiple genes and environmental risk factors are probably involved in its pathogenesis. However, to date, the etiology and pathological mechanism of ASD are still unknown [ 57 ]. The genetic architecture of ASD is complex.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunctional splicing is cell type specific, with neurons being least capable of splicing the mutated pre-mRNA and hence being the cell type most impaired in FD (Slaugenhaupt et al 2001; Cuajungco et al 2003). The Elp1 protein is a key scaffolding subunit of the six-subunit Elongator complex which is essential for tRNA wobble uridine (U34) modifications; in the absence of a functional elongator complex, additions of thiol and methoxycarbonyl-methyl do not occur, which perturbs the translation of mRNAs that preferentially use either AA- or AG-ending codons (Huang et al 2005; Bauer and Hermand 2012; Karlsborn et al 2014; Kojic et al 2021). Consequently, loss of Elp1 function leads to considerable changes in the cellular proteome, which can also indirectly perturb the cellular transcriptome, both of which negatively impact pathways that are critical for neurogenesis and survival (George et al 2013; Chaverra et al 2017; Ohlen et al 2017; Goffena et al 2018; Kojic et al 2021).…”
Section: Introductionmentioning
confidence: 99%